An intriguing middle-sized horse from Coste San Giacomo (Anagni Basin, central Italy). Issue 2 (24th March 2017) - Palombo, Maria Rita; Alberdi, Maria Teresa; Bellucci, Luca; Sardella, Raffaele
Abstract: Various species and ecomorphotypes of the genus Equus are recorded in several southern European Early Pleistocene local faunal assemblages (LFAs), though their taxonomy, phylogenetic relationships, and chronological distribution are still a matter of debate. This article aims to increase knowledge on the European pre-Olduvai stenonoid horses by describing and discussing the equid sample from the middle Villafranchian (Gelasian) Italian site of Coste San Giacomo (CSG; Anagni). Although horse remains from CSG are scanty, the morphological traits, dimensions, and proportions of teeth and some limb bones suggest some affinities with middle-sized European stenonoid horses, in particular with Equus senezensis, as supported by statistical analysis. This opens a new window on the possible phylogenetic relationships of the middle-sized, slender middle Villafranchian horses, although some questions about their actual taxonomic rank cannot be firmly answered based on available data. The complex relationship among environment, structure of the accompanying mammalian fauna, and the presence in the Early Pleistocene LFAs of only one equid, large or middle-sized, or even of more horse species with different size is briefly discussed.